Advertising and integrated brand promotion - O'Guinn, Thomas C. (Thomson/South-Western, 2006)
ADVERTISING AND INTEGRATED BRAND PROMOTION, 4th Edition is highly visual and provides an integrated learning experience for the student. The new edition continues the tradition of delivering a solid understanding of advertising strategy, through a clearly written text as well as through the most contemporary ads. The table of contents follows the same process as an advertising agency. Like other aspects of business, good advertising is the result of hard work and careful planning. The new edition of Advertising and Integrated Brand Promotion illustrates how to best accomplish this.